Cloned airway basal progenitor cells to repair fibrotic lung through re-epithelialization - Yu Zhao; Yueqing Zhou; Weipan Zhang; Mingzhe Liu; Jun Duan; Xiaopeng Zhang; Qiwang Ma; Yujia Wang; Yuzhen Zhang; Zhongliang Guo; Ting Zhang; Wei Zuo (Nature Communications)
Abstract Irreversible damage of the lung epithelium in idiopathic pulmonary fibrosis (IPF) patients causes high mortality worldwide, with no lung repair approaches available currently. Here we show that in murine and monkey models, the KRT5+ P63+ progenitor cells in airway basal layer can enter the alveolar area post fibrotic injury. Aided with an automated culture system, we clone and characterize airway basal progenitor cells from 44 donors with various lung conditions. Transplantation of human progenitor cells into the mouse lung efficiently re-epithelializes the injured alveolar area, forms new respiratory tract and saccule-like structures, which ameliorates fibrotic lesions and improves survival of mice. Mechanistically, the engrafted human progenitor cells do not function by differentiating into mature alveolar cells in mouse lung; instead, they differentiate into saccular cells expressing multiple tight junction proteins such as CLDN4, which help the lung to re-establish epithelial barriers. Furthermore, by cloning P63+ airway basal progenitors from larger mammals and birds, we construct multiple lung-chimerism animals and uncover the evolutionarily conserved roles of these progenitor cells in lung repair. Overall, our data highlight the fate of airway basal progenitor cells in fibrotic lung and provide a potential therapeutic strategy for pulmonary diseases that lack inherent recovery mechanisms.